Overexpression of GmWRKY172 enhances cadmium tolerance in plants and reduces cadmium accumulation in soybean seeds - Xian, Peiqi; Yang, Yuan; Xiong, Chuwen; Guo, Zhibin; Alam, Intikhab; He, Zihang; Zhang, Yakun; Cai, Zhandong; Nian, Hai (Frontiers in Plant Science, 2023)
Cadmium (Cd) stress poses a serious threat to the growth and safety of soybean production. Therefore, improving Cd tolerance in soybean has become the focus and purpose of our research. The WRKY transcription factor family is highly associated with a number of abiotic stress response processes. In the present study, we identified a WRKY transcription factor (GmWRKY172) from soybean that was significantly upregulated by Cd stress, highly expressed in leaves and flowers, and exhibited nuclear localization and transcriptional activity. We also generated GmWRKY172-overexpressing transgenic Arabidopsis and soybean, and found that the transgenic plants exhibited significantly enhanced Cd tolerance and reduced Cd content in shoots compared to wild-type (WT) plants. Additionally, lower Cd translocation from roots to shoots and to seeds were also observed in transgenic soybean. Under Cd stress, transgenic soybean accumulated less malondialdehyde (MDA) and hydrogen peroxide (H2O2) than WT plants, accompanied by higher flavonoid and lignin contents, and peroxidase (POD) activity. RNA sequencing analysis confirmed that many stress-related pathways were regulated by GmWRKY172 in transgenic soybean, including flavonoid biosynthesis, cell wall synthesis, and peroxidase activity. Our findings demonstrated that GmWRKY172 can enhance Cd tolerance and reduce seed Cd accumulation in soybean, providing a promising candidate for the breeding of Cd-tolerant and low Cd soybean.